2014
DOI: 10.1387/ijdb.140277jt
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell division in the Xenopus laevis embryo during gastrulation

Abstract: How vertebrate epithelial cells divide in vivo and how the cellular environment influences cell division is currently poorly understood. A sine qua non condition to study cell division in situ is the ease of observation of cell division. This is fulfilled in the Xenopus embryo at the gastrula stage where polarized epithelial cells divide with a high frequency at the surface of the organism. Recently, using this model system, we have shown that epithelial cells divide by asymmetric furrowing and that the mode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This difference could be due to a number of factors including the distinct structure and molecular components of the junctions, differences in cortical or junctional tension, or differing requirements for barrier function. Previous studies in vertebrates have demonstrated that cells neighboring the cleavage furrow can intercalate between the recently divided cells [27, 63]. This is consistent with our observations that cells initially form a short interface between neighbors, and even one hour after cytokinesis, many daughter cells are still separated by neighbor cells.…”
Section: Discussionsupporting
confidence: 92%
“…This difference could be due to a number of factors including the distinct structure and molecular components of the junctions, differences in cortical or junctional tension, or differing requirements for barrier function. Previous studies in vertebrates have demonstrated that cells neighboring the cleavage furrow can intercalate between the recently divided cells [27, 63]. This is consistent with our observations that cells initially form a short interface between neighbors, and even one hour after cytokinesis, many daughter cells are still separated by neighbor cells.…”
Section: Discussionsupporting
confidence: 92%
“…For indirect immunofluorescence, embryos were fixed with 2% trichloroacetic acid (TCA) in F1 1X medium for 2 hours at room temperature, devitelinated, permeabilized in PBS plus 1% triton X-100 (PBST 1%) for 10 minutes and saturated one hour in PBST 0.1% plus BSA 1% as previously described23. They were then incubated with the following antibodies: anti-GFP (I-16, Santa Cruz, clone 7.1 and 13.1 11 914 460 001, Roche), anti-Xenopus C-cadherin (clone 6B6, DSHB), anti-α-catenin (PA1-25081 Thermo Scientific), anti β-catenin (H102, Sc-7199) or anti-p120 catenin (a kind gift of Dr P McCrea).…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate these questions, we have investigated tension applied on cadherin during cell division in Xenopus embryo epithelium. At blastula stage, in situ observation of cell division is possible since polarized epithelial cells divide with a high frequency at the surface of the organism23. We have employed the approach of E-cadherin FRET tension sensor14 in developing Xenopus leavis embryos.…”
mentioning
confidence: 99%
“…All animal experiments were performed in accordance with the approved protocols and guidelines at Rennes 1 University by the Comité Rennais d'Ethique en Matiere d'Expérimentation Animale (C2EA-07) and the French Ministry for Education and Research (3523813). Eggs were fertilised in vitro and embryos were collected as described previously (Hatte et al, 2014). After de-jelling, embryos were placed in 5% Ficoll in F1 buffer (10 mM HEPES pH 7.6, 31.2 mM NaCl, 1.75 mM KCl, 59 μM MgCl 2 , 2 mM NaHCO 3 , and 0.25 mM CaCl 2 ) for microinjection.…”
Section: Preparation Of Xenopus Embryos and Micro-injectionmentioning
confidence: 99%